INKORPORASI SULFUR DALAM PROTEIN ONGGOK MELALUI TEKNOLOGI FERMENTASI MENGGUNAKAN SACCHAROMYCES CEREVISIAE - Wara Pratitis Sabar Suprayogi (Caraka Tani: Journal of Sustainable Agriculture, 2017)
This research was conducted to determine the influence of incubation time and dose of sulphur in organik fermentation with Saccharomyces cerevisiae. This resech was in vitro at Laboratory Animal Nitrition. Departement Animal of Science, Agriculture Fakulty, Sebelas Maret University. This research was condukted for 3 month. The material were used cassava fermented with fungi Saccharomyces cerevisiae. And and the treatment of dose sulphur at 0 and 1500 mg/kg of substrate (water content 60%), time incubatin 2, 3 and 4 day. The result of experiment were analysed using completely randomozed design faktorial 2x3 and each treatment is repeated 3 time. The results of variance analysis showed that cassava fermented with Saccharomyces cerevisia with 3 day incubation time and addition of sulfur 1500 mg/kg can increase organic matter and protein content of biomassa fermentation significantly (p<0,05)but the level of crude fiber showed non significanly effects.